Production and quality assessment of fish burger from the grass carp, Ctenopharyngodon idella (Cuvier and Valenciennes, 1844) - Monjurul Haq; Progga Laboni Dutta; Nadira Sultana; Md. Anisur Rahman (Journal of Fisheries, 2013)
Fish burger was produced from grass carp (Ctenophygodon idella) to assess the feasibility of value addition to this low priced fish in Bangladesh. Different food additives (25% mashed potato, 2% NaCl, 2% soybean oil, 2% spices and 0.6% sugar) were used to enhance the consumer’s acceptance of the fishery product. Consumers' acceptance of the fish burger was determined by sensory evaluation based on its color, flavor, softness or firmness (S/F), chewy/rubbery (C/R) using 10 point scoring system by a group of 10 untrained judges (20-50 years old). The results were found as follows: color (7.25±1.15), flavor (6.67±1.17), S/F (8.47±1.20) and C/R (7.83±1.23). Evaluation of proximate composition showed that the moisture and protein contents in grass carp mince were 79.15±1.16 % and 18.01±0.44 % respectively which were higher than that of fish burger, 69.46±0.89 % and 16.42±0.57 %, respectively. Lipid (6.64±0.15 %) and ash (2.98±0.09 %) contents in fish burger were also higher than fish mince. The pH of fish mince and fish burger was 6.8±0.11 and 6.6±0.05 respectively. Therefore, from simple cost-profit analysis, it can be assumed that business of fish burger in Bangladesh has a very good prospect and it would be profitable.